Disability-adjusted life years associated with COVID-19 in Brazil, 2020 - Cleber Vinicius Brito dos Santos; Lara Esteves Coelho; Guilherme Tegoni Goedert; Paula Mendes Luz; Guilherme Loureiro Werneck; Daniel Antunes Maciel Villela; Cláudio José Struchiner (PLoS ONE, 2025)
Background We quantified the national- and state-level burden of COVID-19 in Brazil and its states during 2020 and contrasted it to the burden from other causes of disease and injury. Methods We used national surveillance data on COVID-19 cases, hospitalisations and deaths between February/2020 to December/2020. We calculated disability-adjusted life years (DALYs) based on the COVID-19 consensus model and methods developed by the European Burden of Disease Network, which includes mild to moderate, severe, and critical COVID-19 cases, long covid and deaths due to COVID-19. We used Brazil DALYs estimates from the Global Burden of Disease Collaborative Network to compare the COVID-19 burden to that from other causes of disease and injury. Results COVID-19’s led to 5,445,785 DALYs, or 2,603 DALYs/100,000, with > 99% of the burden caused by mortality. Males accounted for the largest fraction of DALYs (3,214,905 or 59%) and DALYs per 100,000 population (140,594 or 63%). Most populated states experienced the highest DALYs. However, the DALYs per 100,000 population were higher in the states of Rio de Janeiro (4,504 DALYs/100,000), Amapá (4,106 DALYs/100,000) and Roraima (3,981 DALYs/100,000). Assuming no major changes in disease burden from other causes of disease and injury from 2019 to 2020 in Brazil, COVID-19’s burden would rank as the leading cause of disability in 2020. Conclusions Compared with studies with similar methodology, our findings showed that Brazil experienced the highest COVID-19 burden (per 100,000 population) in the world. COVID-19 severely impacted Brazil’s populational health in 2020, highlighting the lack of effective mitigation efforts.